ChemInform Abstract: Overman Rearrangement and Pomeranz—Fritsch Reaction for the Synthesis of Benzoazepinoisoquinolones to Discover Novel Antitumor Agents. Issue 19 (13th May 2014) - Li, Bo; Wang, Gaihong; Yang, Mu; Xu, Zhijian; Zeng, Bubing; Wang, Heyao; Shen, Jingshan; Chen, Kaixian; Zhu, Weiliang
Abstract Two routes are described for the synthesis of (VII).